Secondary and primary metabolites reveal putative resistance-associated biomarkers against Erysiphe necator in resistant grapevine genotypes - Ciubotaru, Ramona Mihaela; Franceschi, Pietro; Vezzulli, Silvia; Zulini, Luca; Stefanini, Marco; Oberhuber, Michael; Robatscher, Peter; Chitarrini, Giulia; Vrhovsek, Urska (Frontiers in Plant Science, 2023)
Numerous fungicide applications are required to control Erysiphe necator, the causative agent of powdery mildew. This increased demand for cultivars with strong and long-lasting field resistance to diseases and pests. In comparison to the susceptible cultivar ‘Teroldego’, the current study provides information on some promising disease-resistant varieties (mono-locus) carrying one E. necator-resistant locus: BC4 and ‘Kishmish vatkana’, as well as resistant genotypes carrying several E. necator resistant loci (pyramided): ‘Bianca’, F26P92, F13P71, and NY42. A clear picture of the metabolites' alterations in response to the pathogen is shown by profiling the main and secondary metabolism: primary compounds and lipids; volatile organic compounds and phenolic compounds at 0, 12, and 48 hours after pathogen inoculation. We identified several compounds whose metabolic modulation indicated that resistant plants initiate defense upon pathogen inoculation, which, while similar to the susceptible genotype in some cases, did not imply that the plants were not resistant, but rather that their resistance was modulated at different percentages of metabolite expression and with different effect sizes. As a result, we discovered ten upregulated metabolites that distinguished resistant from susceptible varieties in response to powdery mildew inoculation, three of which have already been proposed as resistance biomarkers due to their role in activating the plant defense response.